Simulations of X‐ray diffraction of shock‐compressed single‐crystal tantalum with synchrotron undulator sources. (24th April 2018) - Tang, M. X.; Zhang, Y. Y.; E, J. C.; Luo, S. N.
Abstract : Simulated X‐ray diffraction patterns of shock‐compressed single‐crystal tantalum for polychromatic synchrotron undulator sources at different shock velocities and detection geometries are presented, along with their interpretation. Abstract : Polychromatic synchrotron undulator X‐ray sources are useful for ultrafast single‐crystal diffraction under shock compression. Here, simulations of X‐ray diffraction of shock‐compressed single‐crystal tantalum with realistic undulator sources are reported, based on large‐scale molecular dynamics simulations. Purely elastic deformation, elastic–plastic two‐wave structure, and severe plastic deformation under different impact velocities are explored, as well as an edge release case. Transmission‐mode diffraction simulations consider crystallographic orientation, loading direction, incident beam direction, X‐ray spectrum bandwidth and realistic detector size. Diffraction patterns and reciprocal space nodes are obtained from atomic configurations for different loading (elastic and plastic) and detection conditions, and interpretation of the diffraction patterns is discussed.